Gambaran Minat Beli di Instagram pada Mahasiswa Fakultas Psikologi Universitas Medan Area - Sahala Sihotang; Yudistira Fauzy Indrawan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to describe purchase intention on Instagram among students of the Faculty of Psychology, Universitas Medan Area. This study used a quantitative approach with a descriptive method. The sample consisted of 80 students selected through purposive sampling with the criteria of being active Instagram users, having made online purchases through Instagram, and having purchased at least four times. Data were collected using a purchase intention scale consisting of attention, interest, desire, and action aspects. Data were analyzed using descriptive statistics with SPSS. The results showed that students’ purchase intention was in the high category, with an empirical mean score of 39.81, higher than the hypothetical mean score of 30. The interest aspect obtained the highest mean score, while the attention aspect obtained the lowest score. These findings indicate that Instagram serves as an effective medium in shaping students’ purchase intention through visual content, promotions, testimonials, and easy access to purchasing information.